Sentencing over Objection to Mobilization as Military Reserve: An analysis of National and International Laws - Madjid, Abdul (Brawijaya Law Journal, 2022)
Law Number 23 of 2019 concerning National Resource Management for State Defense does not regulate conscientious objection, which refers to the right of a person to refuse to participate in a war or military service on the grounds of religion and morality. Their absence in such services is replaced by other responsibilities such as working in public health services, providing security, and being involved in other social services. Article 77 Paragraph (1) of Law Number 23 of 2019 expressly provides for sentences that should be imposed on those who refuse to serve as a military reserve, where the rule is not in accordance with the principle of conscientious objection which gives a person the right to refuse on the basis of conscience. This research discusses the legal consequences of the enactment of two rules regarding military service and the application of different conscientious objections.  This study applied normative juridical methods and approaches to examine the consistency and relevance of various statutes and government regulations that govern conscientious objection. This study also used conceptual and statutory approaches to explore why conscientious objection is considered a ground for refusal to participate in conscription according to International Human Rights Law. The findings revealed that the conception of defense and compulsory military service in Indonesia does not leave any chance to guarantee the rights of citizens to refuse to participate in military service according to the conscience and belief of every individual (conscientious objection). This is in contrast to the regulatory provisions of international human rights ratified by Indonesia under the International Covenant on Civil and Political Rights. Additionally, there is a need for clear arrangements regarding conscientious objection and the requirements that must be met by citizens who submit these principles for the rejection of military service in Indonesia.